OLERKIAK - Aresti, G.; Erdozaincy-Etchart, Arnaud; Won Schiller, Friedrich; Mirande, J. (EGAN, 2021)
NULAZ ERRAITEN DUZU... G. ARESTI: BIZKAITARRA ARNAUD ERDOZAINCY ETCHART: EMAZTEKI BAT ENE BIZIAN... ATZERRIKO NESKATILLA FRIEDRICH WON SCHILLER, J. MIRANDE itzulirik: ERRIN-MIN